THE ESTIMATION OF PEATLANDS RESERVE ON CARBON IN THE FOREST AND SHRUBS THAT HAS BEEN DRAINED - Siti Fatimah Batubara; Fahmuddin Agus (Agrotech Journal, 2016)
Global warming and greenhouse gas emissions (GHGs) became a hot issue in the world today. An increased concentration of carbon in the atmosphere becomes one of the serious problems that can affect life on Earth. Peatlands pointed out as one of the sources of GHG emissions. Drainage of peatlands cause decreased water level so that the decomposition process is faster on a layer above the groundwater table, thus affecting the chemical characteristics of peat. In addition to affecting the ground water level, drainage also leads to a decrease in surface height peat soil (subsidence). Given the magnitude of the role of drainage and land use types in affecting carbon stocks and emissions of CO2 on peat soil, this study is to measure carbon stocks and emissions of CO2 on peat soil in forests and shrubs that have been drained. CO2 emissions increase with the closer spacing of the drainage channel that is at a distance of 50 m to 500 m of drainage channels. Meanwhile, at a distance of 5 m and 10 m of the drainage channel can not be concluded because of the condition of ground water that is stagnant at the time of sampling gas, so be very low CO2 emissions. CO2 emissions on the use of forest land are higher than the shrub land.